Cyclosporine A kinetics in brain cell cultures and its potential of crossing the blood–brain barrier. Issue 1 (25th December 2015) - Bellwon, P.; Culot, M.; Wilmes, A.; Schmidt, T.; Zurich, M.G.; Schultz, L.; Schmal, O.; Gramowski-Voss, A.; Weiss, D.G.; Jennings, P.; Bal-Price, A.; Testai, E.; et al.
Highlights: CyclosporinA (CsA) uptake into brain tissue limited by Pgp at the blood–brain barrier. In 2 rodent brain models limited CsA uptake likely due to missing active transport. Stable low CsA content in brain cell in vitro models after repeated exposure. No bioaccumulation and biotransformation, but CsA-induced Cyclophillyn-B depletion. CsA neurotoxicity due to disturbance of the brain homeostasis by Pgp inhibition. Abstract: There is an increasing need to develop improved systems for predicting the safety of xenobiotics. However, to move beyond hazard identification the available concentration of the test compounds needs to be incorporated. In this study cyclosporine A (CsA) was used as a model compound to assess the kinetic profiles in two rodent brain cell cultures after single and repeated exposures. CsA induced-cyclophilin B (Cyp-B) secretion was also determined as CsA-specific pharmacodynamic endpoint. Since CsA is a potent p-glycoprotein substrate, the ability of this compound to cross the blood–brain barrier (BBB) was also investigated using an in vitro bovine model with repeated exposures up to 14 days. Finally, CsA uptake mechanisms were studied using a parallel artificial membrane assay (PAMPA) in combination with a Caco-2 model. Kinetic results indicate a low intracellular CsA uptake, with no marked bioaccumulation or biotransformation. In addition, only low CsA amounts crossed the BBB. PAMPA and Caco-2 experiments revealed that CsA is mostly trapped to lipophilic compartments and exits the cell apically via active transport. Thus, although CsA is unlikely to enter the brain at cytotoxic concentrations, it may cause alterations in electrical activity and is likely to increase the CNS concentration of other compounds by occupying the BBBs extrusion capacity. Such an integrated testing system, incorporating BBB, brain culture models and kinetics could be applied for assessing neurotoxicity potential of compounds.